2020
DOI: 10.1155/2020/8526581
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous Acid-Producing Bacteria from Catfish (Clarias sp.) with Antibacterial Activity against Selected Fish Pathogens: A Preliminary Study

Abstract: In this study, the application of an autochthonous microorganism as probiotic on catfish (Clarias sp.) was scarcely reported. This study aimed to obtain probiotic candidates from the digestive tract (intestinal and gastric) of catfish. A total of nine isolates were successfully isolated from the catfish. Almost all bacterial colonies were morphologically round, had flat edges, were yellow, and produced clear zones as a sign of producing acid during culture. The analysis showed that the three isolates had the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Similar work has been done with the walking catfish ( Clarias spp. ), where bacterial strains with activity against pathogens were isolated from the host species of interest (Paul et al., 2022; Prihanto et al., 2020). A challenge with Aeromonas veronii after a feeding trial indicated walking catfish fed the diet containing an autochthonous Bacillus strain had higher survival than fish fed the basal diet (Paul et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similar work has been done with the walking catfish ( Clarias spp. ), where bacterial strains with activity against pathogens were isolated from the host species of interest (Paul et al., 2022; Prihanto et al., 2020). A challenge with Aeromonas veronii after a feeding trial indicated walking catfish fed the diet containing an autochthonous Bacillus strain had higher survival than fish fed the basal diet (Paul et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported less LAB obtained from Channa sp., Puntioplites waandersi, and farmed Clarias sp. with only eight, five, and nine bacterial isolates respectively (Agustina et al 2022;Bayu et al 2023;Prihanto et al 2020). Physiological and environmental factors may play a vital role in the LAB diversity among fish species particularly water and feed quality.…”
Section: Discussionmentioning
confidence: 99%